Contrasting effects of prenatal life stress on blood pressure and body mass index in young adults. Issue 4 (April 2015) - Bhat, Sunil K.; Beilin, Lawrence J.; Robinson, Monique; Burrows, Sally; Mori, Trevor A.
Abstract : Background: Various environmental stressors in pregnancy have been reported to affect high blood pressure (BP) in adult offspring. However, few studies have examined the effect of prenatal maternal psychological stress on offspring BP and BMI in early adulthood. Method: In 957 Raine cohort participants, regression analyses were used to examine the association between the count of maternal life stress events experienced during pregnancy and offspring BP and BMI at age 20. Results: Prenatal life stress associated positively with offspring BMI but inversely with SBP. After adjustment for confounders each additional prenatal life stress event reduced offspring SBP by 0.66 mmHg ( P = 0.013) in those with an average BMI and lowered the odds of systolic (pre)hypertension by 17% (odds ratio = 0.83; P = 0.008). The inverse relationship between prenatal life stress and adult SBP was stronger in offspring with higher BMI. On the contrary, each unit increase in prenatal life stress score predicted a BMI increase of 0.37 kg/m 2 ( P = 0.022). Longitudinal analysis showed similar effects of prenatal life stress for offspring BMI from age 8 and SBP from age 14. Conclusion: This study has shown that maternal stress in pregnancy significantly associated with BMI from early childhood, but contrary to our hypothesis predicted lower resting SBP and lower odds of systolic (pre)hypertension in young adult offspring. The effect of prenatal life stress on BP was accentuated by a higher BMI. Fetal programming events as a result of prenatal stress may underpin some of these relationships. Abstract : Supplemental Digital Content is available in the text